Successful Treatment of Postoperative External Biliary Fistula by Selective Nasobiliary Drainage. Issue 2 (1992) - Vagianos, C.; Polydorou, A.; Karatzas, T.; Vagenas, C.; Stavropoulos, M.; Androulakis, J.
Abstract : A 25-year old man presented with a high output external biliary fistula after an operation for a giant hydatid cyst of the liver. Endoscopic sphincterotomy was inadequate to close the fistula. A nasobiliary tube was selectively inserted into the leaking hepatic duct and bile was continuously aspirated. The fistula and the residual cavity healed completely. Details of the patients' management using this alternative technique, are discussed.